Eutanasia dalam Perspektif Hak Asasi Manusia dan Hukum Positif di Indonesia - I Gusti Agung Gede Utara Hartawan; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Warmadewa Press, 2020)
Euthanasia legislation has been approved and enforced in European countries such as the Netherlands. This provides a way for the patient's family with an incurable disease to end the patient's life in order to end the patient's suffering. In Indonesia, currently there are no legal norms that regulate euthanasia. This study aims to analyze euthanasia from a human rights perspective and to know euthanasia from a positive legal perspective in Indonesia. Research is included as normative research with a conceptual approach and statutory regulations. The results of this study indicate that euthanasia is contrary to article 28A, article 28G paragraph (2), and article 28I paragraph (1) of the 1945 Constitution of the Republic of Indonesia and articles 338, 340, 344, 345 of the Criminal Code. In the event that there is a request for euthanasia from the patient or the patient's family, the doctor must reject the request and the decision to implement euthanasia should wait for a court decision